2012
DOI: 10.15283/ijsc.2012.5.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Chondrogenic Differentiation of Mesenchymal Stem Cells

Abstract: The methods for cartilage repair have been studied so far, yet many of them seem to have limitations due to the low regenerative capacity of articular cartilage. Mesenchymal stem cell (MSC) has been suggested as an alternative solution to remedy this challenging problem. MSCs, which have extensive differentiation capacity, can be induced to differentiate into chondrocytes under specific conditions. Particularly, this review focused on the effects of growth factors, cell-to-cell interactions and biomaterials in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 49 publications
(53 reference statements)
3
76
0
Order By: Relevance
“…They reported that the articular cartilage defects treated with MSC overexpressing SOX-9 showed the significantly better integration of the repair tissue at the interface with the surrounding normal articular cartilage when compared to the other groups. It is well documented that TGF-β induces expression of a transcriptional factor SOX-9 in its signaling pathway [8]. In our study, we found that SOX-9 expression was greatly increased.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…They reported that the articular cartilage defects treated with MSC overexpressing SOX-9 showed the significantly better integration of the repair tissue at the interface with the surrounding normal articular cartilage when compared to the other groups. It is well documented that TGF-β induces expression of a transcriptional factor SOX-9 in its signaling pathway [8]. In our study, we found that SOX-9 expression was greatly increased.…”
Section: Resultssupporting
confidence: 64%
“…The extracellular matrix is also comprised of other specific collagens such as type IX and XI [17]. Following the increase in SOX-9 mRNA expression, the production of type II collagen, aggrecan, and cartilage oligomeric matrix protein (COMP) is observed [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This differentiation process resembles the endochondral ossification in growth plate . The key in comprehending this process is to understand the role of growth factors and extracellular microenvironment on MSC differentiation toward the different zonal chondrocytes . Thus far, chondrocytes derived from MSC differentiation have a tendency to progress into the hypertrophic stage .…”
Section: Introductionmentioning
confidence: 99%
“…This work aims at investigating differentiation conditions for MSCs to generate proliferative chondrocytes through temporal manipulation of growth factors treatment. Specifically, we aim to study the impact of transforming growth factor beta 3 (TGFβ3) (chondrogeneic inducing factor) and/or fibroblast growth factor 2 (FGF2; proliferation promoting factor) under various treatment periods . Collagen type II (Col2), a biomarker for assessing the chondrogenic differentiation and Ki67, a proliferative marker are evaluated by both qRT‐PCR and nanosensor‐assisted fluorescence imaging (Fig.…”
Section: Introductionmentioning
confidence: 99%